Importance of Lactobacilli for Human Health - Piotr B. Heczko; Milena Giemza; Weronika Ponikiewska; Magdalena Strus (Microorganisms)
As an extraordinarily diverse group of bacteria, lactobacilli are now classified into several genera, many of which still include “Lactobacillus” in their names. Despite their names, this group of lactic acid bacteria comprises microorganisms that are crucial for human health, especially during the early development of the human microbiota and immune system. The interactions between lactobacilli and components of the mucosal immunity lead to its shaping and development, which is possibly considered a prime mover in the advancement of the human immune system. Although much of the evidence backing the pivotal role of lactobacilli in maintaining human health comes from studies on probiotics aiming to elucidate the mechanisms of their functional activities and studies on mucosal immunity in germ-free mice, it is justifiable to extend observations on the properties of the individual probiotic Lactobacillus that are related to health benefits onto other strains sharing common characteristics of the species. In this review, we will discuss the acquisition, presence, and functions of lactobacilli in different human microbiota throughout their whole life, including those arising in the amnion and their interactions with mucosal and immune cells. Examples of immune system modulation by probiotic lactobacilli include their colonic competition for available nutrients, interference with colonization sites, competition for binding sites on gut epithelial cells, bacteriocin production, reduction of colonic pH, and nonspecific stimulation of the immune system.